PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL DAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN REAL ESTATE DI BURSA EFEK INDONESIA - Nurwahidah, Nurwahidah; Husnan, Lalu Hamdani; AP, I Nyoman Nugraha (Jurnal Magister Manajemen, 2019)
This Research Method uses Linear Regression and Intervening Regression Analysis (IRA). This study aims to analyze the influence of managerial ownership on firm value with Capital Structure and Profitability as an intervening variable. The sampling technique used was purposive sampling and obtained a sample of 10 real estate companies with a research period of 2014-2018. This type of research is associative causal. The data analysis technique in this study is the path analisys (path analysis) using SPSS software ver. 24 with a significant level of 0.05 percent. The results showed that managerial ownership has a positive and significant effect on firm value, managerial ownership has a negative and not significant effect on capital structure and profitability. Capital structure has a negative and not significant effect on firm value while profitability has a positive and significant effect on firm value. Capital structure intervenes but not significantly managerial ownership of firm value. Similarly, profitability intervenes but there is no significant effect of managerial ownership on firm value. Keywords: Managerial ownership, Profitability, Capital Structure, Firm Value